Factors Related to Practice on DPT Vaccine Distribution and Storage - Rahayu, Fitri (Jurnal Berkala Epidemiologi, 2014)
ABSTRACTThe diptheria outbreak in Surabaya indicated that immunization program failure. Immunization is primary preventif effort to decrease morbidity of disease. An immunization service is very important to protect vaccine quality through cold chain so that vaccine potency be optimal. The purpose of this study was to analysis of factors which are assosiated with midwiveâs practice of DPT vaccine distribution and storage to outreach. This study is applying observational approach using cross sectional method. Populations are all village midwives in public health center East Surabaya. The numbers of sample were 38 midwives taken using simple random sampling. The dependent variable was midwiveâs practice of DPT vaccine distribution and storage to outreach and the independent variables of this study were work duration, a history of training of cold chain, sosialization, knowledge, attitude. Primary data were obtained through observation and interview. The results showed that 68.4 % midwiveâs practice on DPT vaccine distribution and storage at outreach is good. Independent variable which are significant assosiated with midwiveâs practice on DPT vaccine distribution and storage at outreach is sosialization about vaccine distribution and storage (p = 0.026) and value of phi and Cramerâs V = 0.431. Enhancement of socialization again be needed to village midwive as efforts for increase knowledge and attitude.Keywords: midwive, cold chain, vaccine distribution, DPT